Exposição aguda e subcrônica ao níquel em peixe-zebra (Danio rerio) : avaliação de parâmetros morfológicos e comportamentais - Nabinger, Débora Dreher (2017)
Metals are some of the more toxic substances in the environment. Nickel is one of them and this heavy metal is naturally present in the earth’s crust. However, excessive levels of nickel lead to environmental contamination and can cause serious and irreversible health problems. The aim of this study was to evaluate the toxicological effects of nickel exposure on cognition and behavior, in larvae and adult zebrafish (Danio rerio). Larvae and adult zebrafish were exposed to four different concentrations (0.025, 2, 5, and 15 mg/L NiCl2) or water (control group) in two treatments: acute and subchronic. Larvae were exposed to NiCl2 for 2 hours (acute treatment: 5-day-old larvae treated for 2 hours) or 11 days (subchronic treatment: 11-day-old larvae treated since fertilization) and adults were exposed for 12 hours (acute treatment) or 96 hours (subchronic treatment). In both treatments, for larvae and adults, exposed animals had a significant concentration-dependent increase in nickel levels compared to control group. For larvae, the survival rate was similar in both treated groups compared to control. However, a significant delay of hatching, a decreased heartbeat rate and morphological alterations (decrease of body length and ocular area at 5 and 8 days post-fertilization, dpf) were observed in subchronically-treated animals. Aversive and exploratory behavior showed no significant differences among doses in acute treatment. In contrast, larvae analyzed at 5 dpf in subchronic treatment displayed differences in exploratory behavior, showing decrease in distance traveled and mean speed, at 0.025 mg/L, whereas there was an increase at same parameters in higher doses (5 and 15 mg/L). Over the 11 days of treatment, the locomotor behavior decreased significantly, at 15 mg/L, at 8 and 11 dpf. Furthermore, subchronic-treated larvae showed impaired aversive long-term memory in the inhibitory avoidance task in high doses analyzed (2, 5 and 15 mg/L). For adults, acute treatment did not alter the locomotor activity. Besides, animals submitted to the concentration of 15.0 mg/L, in subchronic treatment, showed anxiogenic effects. The social behavior was not altered by treatments. However, the exposure to NiCl2 caused a decrease in aggressive behavior (subchronic treatment) and impaired memory (acute and subchronic treatments) in all doses compared to controls. In order to evaluate if nickel exposure produced alterations in the hematological system, we analyzed different blood cells in adult animals. The results showed that treated animals submitted to the concentration of 2.0 mg/L, in acute and subchronic treatment, presented an increase of monocytes. Furthermore, to verify if the behavioral alterations observed in treated animals were related to mechanisms of neuronal death, analyzes of apoptotic death in larvae and specific markers of neuronal death in larvae and adults were performed. The results of apoptotic death demonstrated a significant increase in cell death in acutely treated larvae at a concentration of 15 mg/L. In the subchronic treatment, at 5 dpf, there was an increase in apoptotic death at concentration of 5 mg/L, at 8 dpf, in concentrations of 5 and 15 mg/L and at 11 dpf, in concentrations of 2 and 5 mg/L. In the analysis of specific markers of neuronal death, the results suggest that NiCl2 concentrations tested in larvae and adults did not alter the protein levels of cell death markers. These results suggest that prolonged exposure to nickel in early life stages of zebrafish development leads to morphological and physiological alterations and cognition and locomotor deficits, whereas it may cause anxiogenic effects, impaired memory and decrease aggressive behavior in adult stage. These morphological and behavioral alterations may be associated to neurotoxic effects damage caused by this metal.